Diversity of the genus Chondrilla L. (Asteraceae) in Eastern Europe - ALEXANDR S. KASHIN; ALENA S. PARKHOMENKO; ANNA O. KONDRATI; TATIANA A. KRITSKAYA; ARTEM V. BOGOSLOV; IRINA V. SHILOVA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kashin AS, Parkhomenko AS, Kondratieva AO, Kritskaya TA, Bogoslov AV, Shilova IV. 2024. Diversity of the genus Chondrilla L. (Asteraceae) in Eastern Europe. Biodiversitas 25: 1901-1910. The genus Chondrilla (Asteraceae) has a complex taxonomic structure due to widespread apomictic reproduction. This study aimed to identify the variability and clarify the status of Chondrilla species growing in Eastern Europe (European Russia and Western Kazakhstan). The study of morphological variability in Chondrilla species was assessed using 28 morphometric parameters. Moreover, 840 specimens from 28 populations of 8 Chondrilla species from Eastern Europe were analyzed. Principal Component Analysis (PCA), Nonmetric Multi-Dimensional Scaling (NMDS), recursive decomposition, and random forest algorithm were used for analysis. The ordination methods divided the studied samples into two groups: the first group included samples of C. ambigua and C. pauciflora, and the second group included all remaining samples. Following the resulting binary trees, obtained by recursive decomposition method and the random forest algorithm, a determination key was compiled for the Chondrilla species of Eastern Europe. The high level of morphological variation in Chondrilla and its distribution characteristics revealed in this study by numerical taxonomy and recursive decomposition methods, along with our previous studies results, show that only C. ambigua is a morphologically and genetically well-separated species, including C. pauciflora as a triploid cytotype; C. canescens, C. graminea, C. latifolia and C. juncea are synonyms with the priority name C. juncea and should be considered as subspecies; and C. brevirostris and C. laticoronata are hybrids with C. ambigua as maternal parent.